Pemberdayaan Masyarakat dan Pengelolaan Ekowisata D’Bendungan View Telaga Tunjung Sebagai Wahana Rekreasi Wisata Alam Pedesaan - I Made Wimas Candranegara; I Wayan Mirta; I Nyoman Mangku Suryana; I Putu Eka Mahardhika (Universitas Warmadewa, 2019)
Abstrak The research was conducted by holding a lecture on community empowerment and the management of the ecotourism area of D'bendungan View Telaga Tunjung which was attended by 45 people consisting of managers, the Tabanan Regency Government and the local village community. This research uses the method of solving the steps of the problem-based learning method or problem solving method, namely the existence of problems that are considered important, formulating problems, analyzing hypotheses, collecting data, analyzing data, drawing conclusions, applying the conclusions obtained and reassessing the whole process of solving problem. Whereas the evaluation of activities uses the criteria reference evaluation, including tests before the training is conducted, tests during the training process, tests are given at the end of the training process. The results found activities include local village communities through Paiketan Krama Rantau Timpag (PAKERTI) as the manager of D'Bendungan View can find out and be able to explore their potential, especially related to ecotourism development. The government through the Department of Tourism in collaboration with the manager of 'Dendungan View is able to make a system (management) related to the management of Ecotourism. There is a synergy between the Government of Tabanan Regency through the Tabanan Regency Tourism Office in determining and including Dendungan View as an ecotourism area so that in the future Dendungan View will be one of the tourist destinations in Tabanan Regency. There are social and economic impacts felt by the local village after the implementation of this program. Keywords: Community empowerment, ecotourism area Abstrak Penelitian ini dilaksanakan dengan mengadakan ceramah tentang pemberdayaan masyarakat dan pengelolaan Kawasan ekowisata D’Bendungan View Telaga Tunjung yang diikuti oleh 45 orang yang ada terdiri dari unsur pengelola, Pemerintah Kabupaten Tabanan dan masyarakat desa setempat. Penelitian ini menggunakan metode pemecahan dengan langkah-langkah metode pembelajaran berbasis masalah atau metode problem solving yaitu adanya masalah yang dipandang penting, merumuskan masalah, analisis hipotesis, mengumpulkan data, analisis data, mengambil kesimpulan, penerapan dari kesimpulan yang diperoleh dan menilai kembali seluruh proses pemecahan masalah. Sedangkan evaluasi kegiatan menggunakan evaluasi acuan kriteria, antara lain tes sebelum pelatihan dilaksanakan, tes disela-sela proses pelatihan, tes diberikan pada saat akhir proses pelatihan. Hasil kegiatan pengabdian masyarakat ini diantaranya masyarakat desa setempat melalui Paiketan Krama Rantauan Timpag (PAKERTI) selaku pengelola D’Bendungan View dapat mengetahui dan mampu menggali potensi yang dimilikinya khususnya berkaitan dengan pengembangan ekowisata. Pihak pemerintah melalui Dinas Pariwisata bekerjasama dengan pengelola D’Bendungan View mampu membuatkan sistem (manajemen) terkait pengelolaan Ekowisata. Adanya sinergisitas antara Pemerintah Kabupaten Tabanan melalui Dinas Pariwisata Kabupaten Tabanan dalam menetapkan dan memasukkan D’Bendungan View sebagai kawasan ekowisata sehingga kedepannya D’Bendungan View menjadi salah satu tujuan wisata di Kabupaten Tabanan. Adanya dampak sosial dan ekonomi yang dirasakan oleh desa setempat setelah terlaksananya program ini. Kata kunci: Pemberdayaan masyarakat, kawasan ekowisata